2016
DOI: 10.1128/cvi.00554-15
|View full text |Cite
|
Sign up to set email alerts
|

The Secreted Protein Rv1860 of Mycobacterium tuberculosis Stimulates Human Polyfunctional CD8+T Cells

Abstract: ؉ T cell-dominated responses as previously reported in other cohorts. We further identified a peptide spanning amino acids 21 to 39 of the Rv1860 protein with the potential to distinguish latent TB infection from disease due to its ability to stimulate differential cytokine signatures in HV and PAT. We suggest that a TB vaccine carrying these and other CD8؉ T-cell-stimulating antigens has the potential to prevent progression of latent M. tuberculosis infection to TB disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
1
18
0
1
Order By: Relevance
“…Using an in vitro model, it has been demonstrated that LAM has a direct effect on cells, affecting cellular differentiation and functionality . It has recently been suggested that the generation of TB vaccines carrying CD8 + T cells stimulates antigens that have the potential to prevent the progression of latent TB infection to TB diseases . Thus, our results provide new knowledge regarding the status of CD8 + cells in peripheral blood under Mtb infection.…”
Section: Discussionsupporting
confidence: 81%
“…Using an in vitro model, it has been demonstrated that LAM has a direct effect on cells, affecting cellular differentiation and functionality . It has recently been suggested that the generation of TB vaccines carrying CD8 + T cells stimulates antigens that have the potential to prevent the progression of latent TB infection to TB diseases . Thus, our results provide new knowledge regarding the status of CD8 + cells in peripheral blood under Mtb infection.…”
Section: Discussionsupporting
confidence: 81%
“…Definitions for LTBI patients were heterogeneous and highly variable across studies. Overall 14/34 (41%) studies included a control group of healthy participants who had negative test results for interferon gamma-release assays /tuberculin skin test and/or no known history of or exposure to aTB ( 19 , 22 , 24 , 28 , 29 , 32 , 34 , 35 , 37 , 38 , 43 , 47 , 48 , 50 ). A further 2/34 (6%) studies included exposed individuals into the control group as long as they stayed healthy (e.g., no symptoms and microbiologically negative or tuberculin skin test negative) ( 32 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antigens of the Ag85 complex (Ag85A, Ag85B, Ag85C) have been extensively studied and were included in a number of studies selected in this review. In the newer studies those antigens were mostly included as “classical” and “reference” antigens ( 29 , 39 , 41 , 48 ), however three older studies, recruiting patients in South America reported more in-depth results ( 18 , 19 , 49 ). Schwander et al reported stimulation with Ag85A and Ag85B resulted in significantly higher IFN-γ producing T cells in both PBMCs and broncho-alveolar cells of household contacts in a short-term assay compared to healthy controls ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Diduga perbedaan HLA menyebabkan respons imun yang berbeda pada tiap individu. 30 Kadar IL-4 Pasca Stimulasi Antigen Fusi rESAT-6-CFP-10 pada kelompok TB aktif, TB laten dan orang sehat Kadar IL-4 pasca stimulasi pada kelompok TB laten lebih rendah dibandingkan TB aktif karena mekanisme sistem imun yang menghambat produksi IL-4 pasca stimulasi dengan antigen spesifik Th1. Produksi sitokin IL-4 dihambat oleh IFN-γ dan IL-2 pada kadar yang tinggi pada orang sehat maupun TB laten berperan aktif untuk menghambat produksi IL-4.…”
Section: Kadar Tnf-α Pasca Stimulasi Antigen Fusi Resat-6-cfp-10 Padaunclassified